Intraocular lens power calculation after laser refractive surgery: corrective algorithm for corneal power estimation - Jin, Haiying; Holzer, Mike P.; Rabsilber, Tanja Marina; Borkenstein, Andreas; Limberger, Il-Joo; Guo, Haike; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2010)
PURPOSE: - To evaluate an algorithm for corneal power estimation in intraocular lens (IOL) power calculation after myopic laser refractive surgery using direct corneal measurements. - SETTING: - International Vision Correction Research Centre, University of Heidelberg, Heidelberg, Germany. - METHODS: - Corneal parameters in normal eyes and eyes of refractive surgery cases were evaluated by rotating Scheimpflug imaging. Corneal optical power (Koptical) calculated by a Gaussian optics formula was simplified as Koptical = Kanterior + K2 (Kanterior = anterior corneal power; Kposterior = posterior corneal power; K2 = Kposterior − Kanterior × Kposterior × corneal thickness/1.376). The variation and change in K2 induced by refractive surgery were analyzed. A corrective algorithm to calculate Koptical using mean K2 (−6.10 diopters [D]), Kcorrective = 1.114 × measured K − 6.10, was derived based on statistical analysis, which was in accordance with the modified Maloney method. The IOL power after refractive surgery was calculated using Kcorrective. - RESULTS: - The mean K2 of normal and post-refractive corneas was −6.10 ± 0.23 D and −6.16 ± 0.17 D, respectively (P = .17). The mean refractive surgery-induced change in K2 was −0.06 ± 0.10 D. The variations in K2 were small (95% confident interval, −6.55 to −5.65 [normal cornea]; −6.48 to −5.70 [pre-refractive]; − 6.49 to −5.83 [post-refractive)]. Using Kcorrective for IOL power calculation in post-refractive cases yielded mean absolute prediction errors of 0.58 ± 0.52 D (Haigis), 0.59 ± 0.49 D (double-K Hoffer Q), and 0.58 ± 0.47 D (double-K SRK/T). - CONCLUSION: - The algorithm that induced low error in corneal power estimation was relatively reliable in IOL calculation after myopic laser refractive surgery. - Financial Disclosure: - No author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 24.08.2023